Potential and limitations of local tree ring records in estimating a priori the growth performance of short-rotation coppice plantations. (September 2016) - Trnka, Miroslav; Fischer, Milan; Bartošová, Lenka; Orság, Matěj; Kyncl, Tomáš; Ceulemans, Reinhart; King, John; Büntgen, Ulf
Abstract: As bioenergy plantations are a relatively new phenomenon, long-term experimental data on their productivity and tolerance to environmental stress that provides a robust framework for site selection and potential productivity assessment is still lacking. To address this need, we developed a method to correlate the productivity of bioenergy plantations with local climate using tree-ring chronologies. Tree-ring width from 37 Populus nigra (age > 115 y) and 368 poplar hybrid ( Populus nigra  ×  Populus maximowiczii ) (9–12 y) individuals were collected and analyzed at demonstration sites in the Czech Republic. The growth of mature, naturally grown solitary native trees and young congeneric hybrids grown in high density (∼10, 000 ha −1 ) showed statistically significant correlations (r = 0.71, p < 0.05). Further, we found significant (p < 0.05) and consistent growth responses to changes in key seasonal climatic parameters (e.g., mean air temperature, number of dry days or cumulative heat sum (degree-days) during the growing season) for both natives and their hybrids. The analysis of climate conditions and the tree-ring records revealed a gradual change of climatic conditions since the 1930s, positively affecting poplar growth and indicated that longer rather than shorter harvest cycles are preferable to ensure stable yields at our experimental site. Highlights: We investigated responses of hybrid poplar at plantation and solitary Populus nigra trees. We test the mature tree-ring response as proxy for hybrid plantation suitability. Solitary P. nigra trees and the plantations responded similarly to climate drivers. Method used allows estimating the risk of a very low harvest and best harvest period.